Management of Facilities and Infrastructure in Teaching and Learning Activities at SMPN 1 Wates - Devina Istighfarin; Bunga Amarilis Rizky Mauludy; Farid Setiawan (Penerbit Hellow Pustaka, 2024)
Management of facilities and infrastructure during learning activities is an important aspect in the education system. Facilities and infrastructure include all facilities in the form of equipment and tools used to support teaching and learning activities in an educational institution. Good management in this case aims to support the creation of an effective and efficient environment for students and teachers in achieving educational goals. This research outlines the importance of management of facilities and infrastructure when learning activities are taking place. In this context, management includes planning, organizing, supervising and controlling aspects of facilities and infrastructure. These steps help educational institutions to manage their resources more effectively. This management of facilities and infrastructure ensures that all existing facilities are well maintained, managed efficiently, and always ready to support teaching and learning activities.